2018
DOI: 10.1186/s12879-018-3424-y
|View full text |Cite
|
Sign up to set email alerts
|

Using simultaneous amplification and testing method for evaluating the treatment outcome of pulmonary tuberculosis

Abstract: BackgroundTo evaluate the utility of Simultaneous Amplification and Testing (SAT-TB) Method for monitoring anti-TB treatment response.MethodsSerial morning sputum specimens were obtained from 377 active pulmonary tuberculosis (PTB) cases at baseline, weeks 2, months 2, 5 and 6 (newly diagnosed patients) or 8 (previously treated patients) for AmpSure assay, smear fluorescence microscopy (FM) and BACTEC MGIT 960 culture assay.ResultsAfter treatment of 2 weeks, sputum culture was positive in 280 patients (74.27%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Forty-nine biomarkers were evaluated in just one study. Most of the biomarkers were host-response markers, with the exception of lipoarabinomannan (LAM) in urine, sputum, and plasma ( 30 , 34 , 48 , 86 ), 16s rRNA in sputum ( 39 , 41 , 42 , 75 , 87 ), 85B mRNA in sputum ( 19 , 60 , 64 , 81 ), and IS6110 insertion element in sputum ( 60 ). Among the host-response biomarkers, most biomarkers were cytokine proteins measured in blood, both proinflammatory (e.g., IL-1, IL-6, and TNF-α) and anti-inflammatory (e.g., IL-4 and IL-10), which were most commonly analyzed using plasma or serum samples on commercially available research enzyme-linked immunosorbent assay (ELISA) kits.…”
Section: Resultsmentioning
confidence: 99%
“…Forty-nine biomarkers were evaluated in just one study. Most of the biomarkers were host-response markers, with the exception of lipoarabinomannan (LAM) in urine, sputum, and plasma ( 30 , 34 , 48 , 86 ), 16s rRNA in sputum ( 39 , 41 , 42 , 75 , 87 ), 85B mRNA in sputum ( 19 , 60 , 64 , 81 ), and IS6110 insertion element in sputum ( 60 ). Among the host-response biomarkers, most biomarkers were cytokine proteins measured in blood, both proinflammatory (e.g., IL-1, IL-6, and TNF-α) and anti-inflammatory (e.g., IL-4 and IL-10), which were most commonly analyzed using plasma or serum samples on commercially available research enzyme-linked immunosorbent assay (ELISA) kits.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the real-time amplification signal Ct values generated by SAT-TB can be used for the relative quantification of TB bacteria, which may contribute to the clinical management of TB treatment. The continuous dilution of Mtb indicated that SAT-TB detection had high sensitivity with a detectable 100 CFU/ml ( 16 ). Of the 119 patients without TB who were included, 22 with obsolete TB tested negative for SAT-TB, indicating that this test could evaluate the evolving trend of patients with TB.…”
Section: Discussionmentioning
confidence: 99%
“…The positive result of SAT could indicate treatment failure after 5 months without waiting for the results from culture. 50 The signal intensity of LAM in the urine of six children with TB/HIV became undetectable 3 months after anti-tuberculosis chemotherapy, suggesting that the LAM concentration in urine might be a potential biomarker to monitor the effectiveness of chemotherapy. 51 Longitudinally detecting the serum concentration of MTB-specific peptide fragments by NanoDisk and high-throughput mass spectrometry also has this effect.…”
Section: Diagnosis Of Active Tb Utilizing Various Targetsmentioning
confidence: 97%